Separation of hexane isomers using ZIF-8 - Henrique, Adriano (2020)
An important process in petrochemical industry is the octane upgrading of gasoline by the separation of paraffin isomers in the range C5/C6. The gasoline obtained from crude oil has a high fraction of linear and monobranched alkanes, which must be converted into isomers with high degree of ramification to improve the research octane number (RON) (Ferreira et al. 2013). The RON is one of the parameters of gasoline quality and as higher its value, better is the combustion, reducing the tendency of a rapid and inefficient detonation of the hydrocarbons. In other words, the combustion occurs like a smooth explosion, improving the performance of the motor (Mendes et al. 2014). The separation of n/iso-paraffins is actually realized by the Total Isomerization Process (TIP), which consist in performing the isomerization of normal paraffins, with low levels of RON to mono or di-branched isomers, and then, the paraffins with a high octane degree are separated from the others (Peralta et al. 2012). The research octane number increase as the branching degree of the paraffin increases. In this way, the objective of this work is to study the separation of hexane isomers using a Metal Organic Framework (MOF) i.e. ZIF-8 (Zeolitic Imidazolate Framework) to improve the octane rating of gasoline in TIP processes. The MOF ZIF-8 shows chemical and thermal robustness and its structure consist of a cubic arrangement with 8 sodalite cages in the corner (Park et al. 2006). In this work, several studies of the adsorption of hexane isomers on ZIF-8 were performed, with an equimolar mixture of: n-hexane (n-HEX), 2,2-dymethilbutane (22DMB), 2,3- dymethilbutane (23DMB), 3-methylpentane (3MP) and 2-methypentane. During those experiments the temperatures and hydrocarbon pressure covers temperatures 373, 423 and 473 K and pressure range 2-10 kPa. Figure 1 shows a typical breakthrough curves for the C6 isomers at hydrocarbon pressure 5 kPa and temperature at 373 K. Figure 1 show that ZIF-8 is capable to perform the kinetic separation of hexane isomers in different classes, where the sorption hierarchy is: nHEX>>>2MP>3MP>>23DMB>22DMB. It is also being developed a numerical package using the Method of Lines (MOL) (Schiesser and Griffiths 2009) in MATLAB code to simulate the breakthrough-curves experiments. From this work, it can be concluded that ZIF-8 can be an efficient separator of hexane isomers in classes: linear>monobrached>dibranched paraffins, with a high impact in the upgrading of actual TIP processes in petrochemical industry.